Glyme-based electrolyte formulation analysis in aprotic lithium-oxygen battery and its cyclic stability. (15th November 2019) - Tang, Michael; Chang, Jia-Cheng; Kumar, S. Rajesh; Lue, Shingjiang Jessie
Abstract: In this work, the effect of electrolyte composition was evaluated on lithium-oxygen (Li–O2 ) battery using carbon cloth air electrode. Seven ether-based solvents were measured for their conductivity, viscosity, contact angle and decomposition temperature. The results were compiled with other physical properties to screen potential solvents for future testing. Diglyme and tetraglyme were identified and each of them was individually mixed with one of four lithium salts, yielding eight combinations of electrolytes. These electrolytes were assembled into Li–O2 batteries and the voltage and capacity data were recorded during cycling discharge/charge test. The effects of organic electrolyte physical properties on the battery impedance and cyclic life were discussed. Among the eight electrolytes, lithium bis(trifluoromethane) sulfonimide (LiTFSI) in tetraethylene glycol dimethyl ether (tetraglyme) resulted in the longest cyclic life at a discharge capacity cutoff of 2000 mAh gPt −1 than other compositions. This performance may be ascribed to the electrolyte's high conductivity, sufficient viscosity and suitable contact angle with the air electrode. Highlights: The aprotic Li–O2 battery electrolyte formulation is investigated. Eight combination of four Li salts and two organic solvents are investigated. LiTFSI in tetraglyme achieves 97 cycles and outperform than other electrolytes. The Li–O2 batteries cycling performance is correlated with electrolyte characteristics.